Design optimization and statistical modeling of cementitious grout containing irradiated plastic waste and silica fume using response surface methodology - Khan, M.I. (Elsevier Ltd, 2021)
This study discusses the influence of replacing ordinary Portland cement (OPC) with irradiated waste polyethylene terephthalate (PET) and silica fume on fresh and hardened properties of cementitious grouts. The effect of PET (normal and irradiated) and silica fume (SF) on flow, drying shrinkage, compressive strength (1-day, 7-days and 28-days) and flexural strength (28-days) of cementitious grouts were investigated. Additionally, an analytical tool response surface methodology (RSM) was used for designing the experiment and statistically analyzing the experimental results. A microstructural investigation was performed on the grout sample by using FESEM with EDX and XRD analysis. Experimental results show that loss in both compressive and flexural strengths was observed when OPC was partially replaced by normal PET, however, some of these strengths were gained back by incorporating irradiated PET. A slight reduction in drying shrinkage was observed with the addition of both normal PET and irradiated PET as compared to control samples. The microstructural investigation results also show that the addition of irradiated PET in cement grout causes the formation of new and unique phases, which help in the densification and refinement of microstructure. The theoretical results from the ANOVA model using RSM analysis were experimentally validated with an error of <5, and hence, good agreement was observed between theoretical and experimental results. Gamma irradiation of PET showed the possibility of using plastic waste as a potential source of raw material for the construction industry. Â© 2020 Elsevier Ltd